Thesis management system / Megala Balakrishnan - Megala , Balakrishnan (2004)
The proposed system, Sistem Latihan Ilmiah (SU) is a web-based system. The objective of Sistem Latihan Ilmiah is to implement a computerized and efficient environment for all the undergraduates who are doing their final year thesis. The V model is chosen as the development methodology for the proposed system. This is because the model allows iteration process, where requirements changes in the middle of the development period, can be taken into consideration to allow the system to evolve for better use. Besides, the V model suits the project most due to its ease of use and simplicity, besides being a powerful development model. The main tools used in the system development are ASP, Windows 2000 Professional, Microsoft Internet Explorer 5.5, Internet information Server 5.0, Macromedia Dreamweaver MX, Microsoft. Front Page, Adobe Photoshop 6.0, VB Script, JavaScript, HTML and Microsoft Access 2000. Few methodology techniques were utilized in the information gathering process. Reviews on existing system on the Internet and survey were conducted in order to gain more information regarding this system. Internet surfing has helped a lot in the information gathering process, besides books and journal references. The system analysis and design processes are conducted to deliver diagrammatic outcomes such as data flow diagrams, context diagram and user interface design which will assist in the system implementation in the later part of the development process.